Risks associated with interventions in road traffic accidents involving electric vehicles - Mérida Fernández, José Antonio (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2024)
The motorization the future gives way to vehicles with electric and hybrid propulsion systems. During this transition, promoted by the highest institutions of European Union, vehicles with the new engines will coexist with vehicles with internal combustion engines. The irruption of electric and hybrid vehicles brings with it a series of specific risk, so that carrying out a rescue by emergency teams can become a risk if certain premises are not taken into account before and during the action. The guarantee of rapid and effective attention the victim of a road accident will go the intervention personnel and, this, the provision of the necessary protective equipment, adequate training for them and the existence of safety protocols, specific actions for the participants.